Factors related to depressive symptomatology in women of reproductive age in Chiapas, Mexico - Gómez Pérez, Español; Salvatierra, Benito; español, Español; Ramírez-López, Dulce K. (Acta Universitaria, 2023)
The objective of this research was to analyze depressive symptomatology (DS) and its risk factors in five groups of women of reproductive age. To this end, a non-probabilistic sampling was used, respecting the minimum sample size of 30 in each group, to carry out the statistical tests. The selection of the participants used the linear snowball technique for a global sample (n = 192). DS was identified through the Hopkins Symptom Checklist-25 (HSCL-25) questionnaire. The results reported a prevalence rate of 21.9%. No significant differences were found between the five study groups (X2 = 0.928; 4 gl; p = 0.920), but a significant association was found between the categories of the variables: marital status (X2 = 13.418; 3 gl; p = 0.004) and residential groups (X2 = 17.845; 5 gl; p = 0.002). It is concluded that DS, more than associated with pregnancy, childbirth or postpartum, has an explanation based on the social determinants of health.